Application of Interval Valued Fuzzy Soft Max-Min Decision Making Method - Zulqarnain, Rana Muhammad; Saeed, Muhammad; Ali, Bagh; Ahmad, Nadeem; Ali, Liaqat; Abdal, Sohaib (International Journal of Mathematical Research, 2020)
In this paper, we study some basic concepts of fuzzy sets, soft sets, fuzzy soft sets, and interval-valued fuzzy soft sets. Secondly, we study the interval-valued fuzzy soft max-min decision-making function and developed the graphical model for the Interval-valued fuzzy soft max-min decision making (IVFSMmDM) method by using Interval-valued fuzzy soft max-min decision-making function. Finally, we used IVFSMmDM for faculty selection in the education department and observed that T4 is the best teacher for teaching by using hypothetical data.